2023
DOI: 10.1021/acs.jafc.3c04786
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Acute Alcoholic Liver Injury via Attenuating Oxidative Damage and Modulating Inflammation by Means of Ursodeoxycholic Acid–Zein Nanoparticles

Dong Wang,
Jing Wang,
Yingchao Wu
et al.

Abstract: Ursodeoxycholic acid (UDCA) has been broadly adopted for the clinical treatment of hepatic and biliary diseases; however, its poor water-solubility becomes an obstacle in wide applications. To overcome these challenges, herein, a two-tier UDCAembedded system of zein nanoparticles (NPs) along with a polyelectrolyte complex was designed under facile conditions. Both the UDCA−zein NPs and their inclusion microcapsules showed a spherical shape with a uniform size. A typical wall plus capsule/core structure was for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Oxidative stress plays an important role in alcoholic liver disease ( Cederbaum et al, 2009 ). MDA, GSH, SOD, and CAT, as oxidative stress biomarkers, are often important indicators reflecting the degree of liver oxidative damage ( Wang et al, 2023 ). The detection results of liver oxidative stress biomarkers MDA, GSH, SOD and CAT showed that GLC could inhibit the expression of MDA, promote the expression of GSH, SOD and CAT, enhance the antioxidant function of liver cells, and alleviate the damage caused by oxidative stress caused by alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in alcoholic liver disease ( Cederbaum et al, 2009 ). MDA, GSH, SOD, and CAT, as oxidative stress biomarkers, are often important indicators reflecting the degree of liver oxidative damage ( Wang et al, 2023 ). The detection results of liver oxidative stress biomarkers MDA, GSH, SOD and CAT showed that GLC could inhibit the expression of MDA, promote the expression of GSH, SOD and CAT, enhance the antioxidant function of liver cells, and alleviate the damage caused by oxidative stress caused by alcohol.…”
Section: Discussionmentioning
confidence: 99%